Landscape Analysis on the Results of Least Cost Paths vs. Real World Paths - Bartel, Amy (My University, 2013)
The purpose of this study was to examine the results of a competitive navigation activity completed by students in a military geography class using various landscape analysis techniques. The goal of the activity was to locate and capture six points before the other team on a predetermined navigation course. Teams of students were provided various forms of geospatial data designed to help them develop a winning strategy for the field event.
Color poster with text, maps, tables, and images.
Keywords: Military geography; War games--Maps; Geospatial data; College students--Wisconsin--Eau Claire; Posters